LEVEL OF DECISION MAKING IN SOME VOLLEYBALL SKILLS (SERVE, RECEPTION, PREPARATION) FOR SECONDARY STAGE STUDENTS - Merzougue, djamel; sebbane, Mohamed (www.sjsr.se, 2015)
The importence of reserch to identify the skilllevel to takedécision in some volleyball skills and hadassumed the existence of researcher statistically significant differences between the decision-making skill and volley-ball oneswith the lowlevel ofeachskill. 148 pupel of the second level of secondary on the city of mostaganem, havebeenchoasenad the resercher has in concludedthatthere are significantdifferencesbetween the decision-makingskills. The resercherrecommended the need to use new methods focus on montalskills in teaching volley-ball skills, and this in order to raise the level of learningaccording to the phases of the age, sex, and potential, italsorecommendedthat the harmfulconductperiodictests and ongoinng mental abilities in order to recagnizetheir reality and thenwork on developingthem.
Keywords: decision-making , volley-ball, heighschool